A Peircean Semiotic Analysis of Elegiac Symbolism in Rithā’ al-Andalus by Abū al-Baqā’al-Rundī - Sulthon, Athian; Ridlo, Ubaid; Alek (Journal of Literature Review, 2025)
ABSTRACT This study investigates Rithā’ al-Andalus by Abū al-Baqā’ al-Rundī through the semiotic lens of Charles Sanders Peirce to examine how poetic language communicates historical grief, spiritual identity, and collective memory. Composed in 1267 CE, the elegy laments the fall of Muslim Andalusia following the Christian reconquest. Beyond a personal outcry, the poem serves as a layered cultural document, encoding ideological resistance and loss through complex sign systems rooted in Islamic tradition and Andalusian history. The primary objective of this research is to analyze how Rithā’ al-Andalus employs Peirce’s triadic model of signs—icon, index, and symbol—to articulate themes of displacement, decline, and spiritual anguish. The study seeks to identify each type of sign within the poem and interpret its function in representing communal trauma and religious dislocation. This research adopts a qualitative interpretive approach. The original Arabic text is subjected to close reading, with poetic expressions classified based on Peircean categories. Each sign is interpreted within its historical, religious, and literary context, drawing on interdisciplinary scholarship in Islamic studies, medieval history, and Arabic poetics. The findings demonstrate that iconic signs evoke vivid visualizations of ruin and sorrow; indexical signs register the traces of temporal loss and cultural fracture; and symbolic signs encapsulate abstract notions of divine will, imperial collapse, and faith. Together, these elements construct a semiotic grammar of mourning. Ultimately, the study concludes that Rithā’ al-Andalus functions as more than a poetic elegy—it emerges as a symbolic archive of Andalusia’s fall and a resilient expression of Islamic identity through semiotic discourse.